Dose prescription in SBRT for early-stage non-small cell lung cancer: are we all speaking the same language?. Issue 3 (June 2021) - Merlotti, Anna; Bonomo, Pierluigi; Ragona, Riccardo; Trovò, Marco; Alongi, Filippo; Mazzola, Rosario; Vigna Taglianti, Riccardo; Gianello, Luca; Reali, Alessia; Bergesio, Fabrizio; Lucio, Francesco; Boriano, Alberto; et al.
Introduction: Stereotactic body radiation therapy is increasingly used in the treatment of early-stage lung cancers. Guidelines provide indications regarding the constraints to the organs at risk (OARs) and the minimum coverage of the planning target volume but do not suggest optimal dose distribution. Data on dose distribution from the different published series are not comparable due to different prescription modalities and reported dose parameters. Methods: We conducted a review of the published data on dose prescription, focusing on the role of homogeneity on local tumor control, and present suggestions on how to specify and report the prescriptions to permit comparisons between studies or between cases from different centers. Conclusions: To identify the dose-prescription modality that better correlates with oncologic outcomes, future studies should guarantee a close uniformity of dose distribution between cases and complete dose parameters reporting for treatment volumes and OARs.